2013
DOI: 10.5811/westjem.2012.3.6882
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation as a Tool for Assessing Decision-Making in Pandemic Influenza Response Training

Abstract: Introduction: We sought to develop and test a computer-based, interactive simulation of a hypothetical pandemic influenza outbreak. Fidelity was enhanced with integrated video and branching decision trees, built upon the 2007 federal planning assumptions. We conducted a before-and-after study of the simulation effectiveness to assess the simulations' ability to assess participants' beliefs regarding their own hospitals' mass casualty incident preparedness.Methods: Development: Using a Delphi process, we finali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Among the few specific findings about key factors in successful training, an exercise involving 17 local health district risk communicators in Georgia, U.S.A., found that participants had much greater difficulty following risk communication principles under the time pressures of a realistic and stressful simulation than they did in a tabletop exercise. Participants did report highly enhanced awareness, readiness, and knowledge after the real-time simulation Ablah, et al, 2007;Dausey et al, 2006;Leaming, et al, 2013;Sandstrom et al, 2014;Uddin et al, 2008; forgetting to include expression of empathy and using too much bureaucratic speech; media talking points not shared with hospitals and other agencies; participants not adequately monitoring media developments; notification lists often used indiscriminately and not usable by back-ups in their current format; departments waiting until they were contacted to start communicating with the public, meaning they often responded defensively and had trouble quickly formulating an initial message that was clear, informative, and alleviated anxiety. In South Africa, hospital preparedness for risk communication and public relations was found to be among the lowest preparedness of areas assessed.…”
Section: F O R P E E R R E V I E W O N L Ymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the few specific findings about key factors in successful training, an exercise involving 17 local health district risk communicators in Georgia, U.S.A., found that participants had much greater difficulty following risk communication principles under the time pressures of a realistic and stressful simulation than they did in a tabletop exercise. Participants did report highly enhanced awareness, readiness, and knowledge after the real-time simulation Ablah, et al, 2007;Dausey et al, 2006;Leaming, et al, 2013;Sandstrom et al, 2014;Uddin et al, 2008; forgetting to include expression of empathy and using too much bureaucratic speech; media talking points not shared with hospitals and other agencies; participants not adequately monitoring media developments; notification lists often used indiscriminately and not usable by back-ups in their current format; departments waiting until they were contacted to start communicating with the public, meaning they often responded defensively and had trouble quickly formulating an initial message that was clear, informative, and alleviated anxiety. In South Africa, hospital preparedness for risk communication and public relations was found to be among the lowest preparedness of areas assessed.…”
Section: F O R P E E R R E V I E W O N L Ymentioning
confidence: 99%
“…(NHLBI tool) Low Leaming, et al, 2013 Computer simulation for decision-making in pandemic influenza response scenario. Purpose: to introduce personnel to critical decisions involved in handling a pandemic influenza surge and assess their opinion of current preparedness at home institution in U.S.A. Used a Delphi process to finalize an 8-week scenario exercise.…”
Section: Heide Man and Hawley 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…Computerized scenarios can also be used to simulate large numbers of patients in an MCI without significant equipment or personnel costs. Computerized scenarios have been used to improve response to a pandemic influenza surge and for mass-casualty planning on a larger scale 8 9 A handful of groups have designed online MCI virtual scenarios for provider education, demonstrating equivalent learning to simulation mannequins 10 and overall receptiveness of participants 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Computerized scenarios have been used to improve response to a pandemic influenza surge and for mass-casualty planning on a larger scale. 8,9 A handful of groups have designed online MCI virtual scenarios for provider education, demonstrating equivalent learning to simulation mannequins 10 and overall receptiveness of participants. 11 A few papers have described interactive computerized games for MCI teaching.…”
Section: Introductionmentioning
confidence: 99%